Antitrypanosomal potential of the red sea soft coral Nephthea mollis supported by metabolomics profiling and molecular docking studies - Khaled M. Allam, Yaser A. Mostafa, Usama R. Abdelmohsen,, Amgad I.M. Khedr, Ahmed E. Allam, Ehab S. Elkhayat, Mostafa A. Fouad (Journal of Applied Pharmaceutical Science, 2023)
The crude extract and its derived ethyl acetate fraction of the soft coral Nephthea mollis displayed remarkable in vitro antitrypanosomal activity against Trypanosoma brucei with IC50 values of 6.4 and 3.7 μg/ml, respectively. Consequently, the crude extract was subjected to LC–HR–ESI–MS metabolomics profiling to identify the constituents that may underlie their bioactivities. As a result, 33 secondary metabolites were characterized, among which sesquiterpenes and diterpenes prevailed. In silico molecular modeling revealed the high binding affinity for the ornithine decarboxylase active site, with five dereplicated compounds having docking scores higher than the cocrystallized ligand. These results highlight N. mollis as a rich source of compounds that might help develop therapies for Human African trypanosomiasis.